The Effects of Distributed Group Support and Process Structuring on Software Requirements Development Teams: Results on Creativity and Quality - Ocker, Rosalie; Hiltz, Starr Roxanne; Turoff, Murray; Fjermestad, Jerry (Journal of management information systems, 1995)
Previous research has indicated that the creative task of deciding upon the initial specifications for a software system can benefit from a structured process to guide group interaction in face-to-face meetings, and can benefit from computer support. This 2×2 experiment is the first to look at the joint effects of a distributed asynchronous computer conferencing mode of communication (CC, as compared with face-to-face), and a structured process, on software design outcomes. Subjects were teams of graduate students in computer science and business, who designed an automated post office as a course assignment. The quality of solution produced by the CC groups was judged to be marginally higher, while CC groups were rated as considerably more creative. There were no main effects for the structured/unstructured factor, or any significant interactions.